An injectable cationic hydrogel electrostatically interacted with BMP2 to enhance in vivo osteogenic differentiation of human turbinate mesenchymal stem cells - Kim, Mal Geum; Kang, Tae Woong; Park, Joon Yeong; Park, Seung Hun; Ji, Yun Bae; Ju, Hyeon Jin; Kwon, Doo Yeon; Kim, Young Sik; Kim, Sung Won; Lee, Bong; Choi, Hak Soo; Lee, Hai Bang; et al. (Materials Science and Engineering C, 2019)
We have designed and characterized an injectable, electrostatically bonded, in situ–forming hydrogel system consisting of a cationic polyelectrolyte [(methoxy)polyethylene glycol-b-(poly(ε-caprolactone)-ran-poly(L-lactic acid)] (MP) copolymer derivatized with an amine group (MP-NH2) and anionic BMP2. To the best of our knowledge, there have been hardly any studies that have investigated electrostatically bonded, in situ–forming hydrogel systems consisting of MP-NH2 and BMP2, with respect to how they promote in vivo osteogenic differentiation of human turbinate mesenchymal stem cells (hTMSCs). Injectable formulations almost immediately formed an electrostatically loaded hydrogel depot containing BMP2, upon injection into mice. The hydrogel features and stability of BMP2 inside the hydrogel were significantly affected by the electrostatic attraction between BMP2 and MP-NH2. Additionally, the time BMP2 spent inside the hydrogel depot was prolonged in vivo, as evidenced by in vivo near-infrared fluorescence imaging. Biocompatibility was demonstrated by the fact that hTMSCs survived in vivo, even after 8 weeks and even though relatively few macrophages were in the hydrogel depot. The osteogenic capacity of the electrostatically loaded hydrogel implants containing BMP2 was higher than that of a hydrogel that was simply loaded with BMP2, as evidenced by Alizarin Red S, von Kossa, and hematoxylin and eosin staining as well as osteonectin, osteopontin, osteocalcin, and type 1α collagen mRNA expression. The results confirmed that our injectable, in situ–forming hydrogel system, electrostatically loaded with BMP2, can enhance in vivo osteogenic differentiation of hTMSCs.
Keywords: Cationic polyelectrolyte; Electrostatic attractions; Injectable hydrogels; Mesenchymal stem cell; Near-infrared fluorescence imaging; Osteogenic capacity; Osteogenic differentiation; Poly (epsiloncaprolactone); Adult; Animals; Bone Morphogenetic Protein 2; Female; Heterografts; Humans; Hydrogels; Mesenchymal Stem Cells; Mice; Osteogenesis; Static Electricity; Stem Cell Transplantation; Turbinates; Electrostatic interaction; Human turbinate mesenchymal stem cells; Injectable hydrogel depot; Osteogenic differentiation